Chimaeribacter arupi a new member of the Yersineacea family has the characteristics of a human pathogen - Riediger, Matthias; Hoffmann, Katharina; Isberner, Riekje; Dreyer, Annika; Tersteegen, Aljoscha; Marquardt, Pauline; Kaasch, Achim J.; Zautner, Andreas E. (Frontiers in Cellular and Infection Microbiology, 2023)
Chimaeribacter arupi (heterotypic synonym: "Nissabacter archeti") is a facultative anaerobic, newly described Gram-negative rod and belongs to the Yersineacea family. Here, we report the case of a 19-month-old female infant patient who presented to the emergency unit with somnolence and fever.C. arupi was isolated from a positive blood culture, taken via an implanted catheter, proving a bloodstream infection by the pathogen. The objective of this study was to utilize whole genome sequencing to assess the genes encoding potential virulence associated factors, which may play a role in host tropism, tissue invasion and the subsequent stages in the pathogenesis of a bloodstream infection with C. arupi.The genome of the isolate was completely sequenced employing Illumina MiSeq and Nanopore MinION sequencing and the presumptive virulence associated factors and antimicrobial resistance genes were investigated in more detail. Additionally, we performed metabolic profiling and susceptibility testing by microdilution.The presence of predicted TcfC-like α-Pili suggests that C. arupi is highly adapted to humans as a host. It utilizes flagellar and type IV pili-mediated motility, as well as a number of γ 1 -pili and a σpilus, which may be used to facilitate biofilm formation and adherence to host epithelia.Additionally, long polar fimbriae may aid in tissue invasion. The bacterium possesses antioxidant factors, which may enable temporary survival in phagolysosomes, and a capsule that potentially Chimaeribacter arupi as human pathogen 2 This is a provisional file, not the final typeset article provides protection from phagocytosis. It may acquire iron ions from erythrocytes through the type 6 secretion system and hemolysins. Furthermore, the isolate exhibits beta-lactamase-mediated penicillin and aminopenicillin resistance.Based on the analysis of the whole genome, we conclude that C. arupi possesses virulence factors associated with tissue invasion and may thus be a potential opportunistic pathogen of bloodstream infections.